2016
DOI: 10.3389/fpls.2016.01771
|View full text |Cite
|
Sign up to set email alerts
|

Single R Gene Introgression Lines for Accurate Dissection of the Brassica - Leptosphaeria Pathosystem

Abstract: Seven blackleg resistance (R) genes (Rlm1, Rlm2, Rlm3, Rlm4, LepR1, LepR2 & LepR3) were each introgressed into a common susceptible B. napus doubled-haploid (DH) line through reciprocal back-crossing, producing single-R gene introgression lines (ILs) for use in the pathological and molecular study of Brassica—Leptosphaeria interactions. The genomic positions of the R genes were defined through molecular mapping and analysis with transgenic L. maculans isolates was used to confirm the identity of the introgress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 69 publications
(140 reference statements)
6
93
0
Order By: Relevance
“…A). As a positive control for the transformation, and to test for any further interference of AvrLm4–7 with R gene recognition, we tested the same transgenic isolates on B. napus Rlm3 control lines (Larkan et al ., ) and, as expected and reported previously (Plissonneau et al ., ), both AvrLm4–7 and AvrLm7 also suppressed the avirulence function of AvrLm3 (Table , Fig. A).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…A). As a positive control for the transformation, and to test for any further interference of AvrLm4–7 with R gene recognition, we tested the same transgenic isolates on B. napus Rlm3 control lines (Larkan et al ., ) and, as expected and reported previously (Plissonneau et al ., ), both AvrLm4–7 and AvrLm7 also suppressed the avirulence function of AvrLm3 (Table , Fig. A).…”
Section: Resultssupporting
confidence: 92%
“…Pathogen growth is blocked by the hypersensitive response of tissues at the margin of the infection site (dark brown ring) compared with a compatible response of Topas DH16516, showing the collapse of almost the entire cotyledon. Brassica napus differential lines Topas‐ Rlm3 , Topas‐ Rlm4 (Larkan et al ., ), Roxet and Goéland containing Rlm3 , Rlm4 , Rlm7 and Rlm9 resistance genes, respectively, were used as positive controls, and the susceptible B. napus cv. Topas DH16516 was used as a negative control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivars Excel and Roxet are Rlm7 cultivars that have been included in previous studies (Clarke et al ., ; Daverdin et al ., ; Larkan et al ., ). In the present study, results confirmed the presence of the Rlm7 genes in these cultivars; in addition, QR against L. maculans was detected in Excel and Roxet using the method of Huang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Canola ( B. napus ) breeding lines, Topas DH16516 (Topas-wild), a double haploid line susceptible to L. maculans and Topas -Rlm2 , an introgression line resistant to L. maculans isolates carrying AvrLm2 (Larkan et al, 2016a,b) were used as plant material. Seven-day old seedlings of both resistant and susceptible canola lines grown under controlled environment were point inoculated with pycnidiospores suspension of L. maculans isolate D5.…”
Section: Methodsmentioning
confidence: 99%